2003
DOI: 10.1097/00002060-200305000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study results show that the dynamic electromyographic signal obtained with wire electrodes is, at minimum, as repeatable as surface electromyograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, the reservations related to generalizing the wire EMG data to the entire muscle – at least in neurologically-intact individuals – are unfounded. Previous work has shown that when the wire EMG signal has been normalized to a reference standard (in this case, a maximum muscle test) there were no significant differences in the wire and surface EMG signal timing or magnitude [ 15 ]. Although surface electrodes could have been used to record data from superficial muscles they could not have been used to record EMG from many of the deep muscles examined here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reservations related to generalizing the wire EMG data to the entire muscle – at least in neurologically-intact individuals – are unfounded. Previous work has shown that when the wire EMG signal has been normalized to a reference standard (in this case, a maximum muscle test) there were no significant differences in the wire and surface EMG signal timing or magnitude [ 15 ]. Although surface electrodes could have been used to record data from superficial muscles they could not have been used to record EMG from many of the deep muscles examined here.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the comprehensive number of muscles examined each study participant performed two self-selected speed walking trials, with data selected from each trial. In normal adults the examined gait parameters are highly consistent across trials [ 15 ], and the use of multiple sessions did not confound the results. The mean gait velocity for these subjects was 81.9 ± 3.7 m per minute.…”
Section: Methods (Overview)mentioning
confidence: 99%
See 1 more Smart Citation
“…All EMG data were subject to a root mean squared moving average of 25 ms. EMG data were normalized to maximum voluntary isometric contractions (MVICs); three MVICs were recorded for each muscle following the completion of walking trials. The MVIC data were recorded for 5 s with a gradual build-up of 2 s prior to maximal effort for the final 3 s. The peak value from a 0.5-s window obtained from the 3-s maximal effort of the MVIC was used as the reference value, similar to the methods reported elsewhere [14, 16]. All participants were verbally encouraged in a standard manner during the MVICs and a 1-min recovery period was set between repetitions.…”
Section: Methodsmentioning
confidence: 99%
“…EMG data was normalised to maximum voluntary isometric contractions (MVIC); three MVICs were recorded for each muscle following completion of walking trials. The MVIC data was recorded against manual resistance for 5 s with a gradual build up of 2 s prior to maximal effort for the final 3 s. The peak value from a 500 ms window obtained from the 3-s maximal effort of the MVIC was used as the reference value similar to the methods used by Bogey et al [17] and Murley et al [18]. All participants were verbally encouraged in a standard manner during the MVICs and a 1-min recovery period was set between repetitions.…”
Section: Methodsmentioning
confidence: 99%